2007
DOI: 10.1097/nen.0b013e318093f3ef
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression After Bone Marrow Transplantation in a Model of Multiple Sclerosis Is Associated With Chronic Microglial and Glial Progenitor Response

Abstract: Multiple sclerosis (MS), the most common nontraumatic cause of neurologic disability in young adults in economically developed countries, is characterized by inflammation, gliosis, demyelination, and neuronal degeneration in the CNS. Bone marrow transplantation (BMT) can suppress inflammatory disease in a majority of patients with MS but retards clinical progression only in patients treated in the early stages of the disease. Here, we applied BMT in a mouse model of neuroinflammation, experimental autoimmune e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…47,48 In the present study, we showed that BM cells did differentiate into NSCs, which, comparable to SVZ-NSCs, can differentiate into neural cells in vitro and in vivo and effectively suppress EAE. It has been found that transplantation of whole BM cells at early stage of disease effectively blocked or delayed EAE development 49 but without effect at chronic stage. 9,49 EAE mice treated with BM-derived mesenchymal stem cells (MSCs) 16,17,50,51 showed a significantly milder disease and fewer relapses compared with control mice, with decreased inflammation infiltrates, reduced demyelination, and axonal loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 In the present study, we showed that BM cells did differentiate into NSCs, which, comparable to SVZ-NSCs, can differentiate into neural cells in vitro and in vivo and effectively suppress EAE. It has been found that transplantation of whole BM cells at early stage of disease effectively blocked or delayed EAE development 49 but without effect at chronic stage. 9,49 EAE mice treated with BM-derived mesenchymal stem cells (MSCs) 16,17,50,51 showed a significantly milder disease and fewer relapses compared with control mice, with decreased inflammation infiltrates, reduced demyelination, and axonal loss.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot clinical trail, autologous MSCs had been injected intrathecally to patients with MS, with a demonstrable benefit in some patients, 52 indicating that BM derived multipotential cells is likely to become a useful clinical tool. The effect of whole BM cells and MSCs on EAE is mainly the result of elimination of pathogenic cells 49 and interference with autoimmune responses, 16,50 but not transdifferentiation into neurons or oligodendrocytes. 16,50 Thus, the neural replacement and remyelination property of BM-NSCs, in addition to their immunoregulatory capacity, provides a significant advantage for these cells over MSCs and whole BM cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 The etiology of this disease is still unclear, but based on altered immune responses in MS patients, the pathology of MS lesions, and its animal model, experimental autoimmune encephalomyelitis, the inflammatory element of MS pathogenesis is believed to be primarily T cell-mediated, possibly as the result of a breakdown in immune tolerance, in particular peripheral mechanisms. 2 Recent thymic emigrants that escape central tolerance can still be susceptible to peripheral tolerance checkpoints such as regulatory T cells (Tregs). Tregs, which are also thymic dependent, increasingly appear to be pivotal in the maintenance of selftolerance, with their elimination leading to the development of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by monitoring of tracking of transplanted green fluorescent protein-transduced cells, the endogenous origin of microglia in advanced disease was shown. Host macrophages/microglial cells demonstrated robust activation and their number was higher in the stage of disease progression [25]. The same demonstration of different local trigger mechanisms can be made for systemic sclerosis (SSc), inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 69%